Penerapan Kebijakan Pendidikan Inklusi Di Tingkat Madrasah Ibtidaiyah - Winda Ramayani; Sarah Puspita; Kurniawaty Kurniawaty; Chaty Suri Hasanah; Wismanto Wismanto (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Elementary schools with inclusive education programs pose challenges for principals and teachers in educational institutions. Inclusive education in elementary schools needs to receive more attention because elementary school students still need full attention from educators, along with the presence of students with special needs. Of course, achieving learning goals is not easy. The aim of this research is to observe and describe the phenomena that occur during the implementation of inclusive education in elementary schools. This research uses a qualitative descriptive method, analyzing the factors that support and hinder the implementation of inclusive education in elementary schools, thus concluding that teachers need to know more about the factors that support and hinder the implementation of inclusive education in Madrasah Ibtidaiyah. The results of this research show that educational service institutions and the community must work together to provide appropriate services to students in general and children with special needs to improve the quality of educational services in schools.